Evaluation of an empirical model for predicting the calorific value of biomass briquettes from candlenut shells and kesambi twigs - Dethan, Jemmy Jonson Sula (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2024)
Biomass briquettes offer a sustainable alternative to conventional fossil fuels, contributing to renewable energy while reducing environmental impact. This research explores the development of biomass briquettes from candlenut shell charcoal (Aleurites moluccanus) and kesambi twigs (Schleichera oleosa), focusing on their physical properties and heating values. Using tapioca as a binder, briquettes were produced with varying ratios: A. Control (90% kesambi twigs + 10% adhesive), B. 3:1 (67.5% kesambi twigs + 22.5% candlenut shell charcoal + 10% adhesive), C. 1:1 (45% kesambi twigs + 45% candlenut shell charcoal + 10% adhesive), and D. 1:3 (22.5% kesambi twigs + 67.5% candlenut shell charcoal + 10% adhesive). The study aimed to optimize briquette composition for maximum density, compressive strength, and calorific value while minimizing moisture, ash, and volatile matter. Results indicated that a higher proportion of candlenut shell charcoal enhanced density, compressive strength, and fixed carbon content, with the highest calorific value exceeding 19 MJ/kg observed in the 1:3 ratio. Additionally, the study evaluated three empirical models for predicting the Higher Heating Value (HHV) of the briquettes, finding the Nhuchhen model to be the most accurate, with an R² value of 0.93, providing a reliable method for predicting calorific value.